The Influence of Financial Due Diligence in M&A on Investment Decision Based on Financial Data Analysis - Li, Wei (European Journal of AI, Computing & Informatics, 2025)
With the gradual growth of enterprise mergers and acquisitions activities, the role of financial due diligence in investment decisions has become increasingly prominent. In the traditional financial due diligence process, due to the constraints of information granularity and analytical tools, potential financial risks cannot be fully revealed. Starting from the analysis of financial data, this article expounds its application value and practical effectiveness in the due diligence process. The research builds an assessment system based on four core dimensions: profitability, debt-paying ability, operational efficiency, and risk identification, and analyzes its role and function in valuation correction, risk early warning, and decision support. The research results show that the data-driven due diligence approach can improve the accuracy of investment decisions, is of great significance for merger and acquisition integration and performance prediction, and promotes the realization of high-quality merger and acquisition transactions.